PROBLEMS OF APPLIED LINGUISTICS - Eshkoraev E.A. (PEDAGOGS, 2024)
Abstract: In this article, the historical overview of the field of applied linguistics, its current issues, as well as interdisciplinary approaches to solving linguistics are discussed.